Epithelial Tight Junctional Changes in Colorectal Cancer Tissues - Xuexuan Wang; Owen Tully; Benjamin Ngo; Marc Zitin; James M. Mullin (The Scientific World Journal)
Colorectal cancer (CRC) is one of the most common cancers in the western world. Early screening and detection could be highly preventative and therefore reduce mortality. Tight junctions (TJ) are well known for their function in controlling paracellular traffic of ions and molecules. It has become increasingly evident that TJs play a crucial role in maintaining cell-cell integrity, and the loss of cell junctional sealing could involve itself in the processes of carcinoma and cancer metastasis. If correlations between altered TJ proteins and CRC presence or invasiveness could be established, they may serve as important markers and guidelines for prophylactic and prognostic purposes, along with other screening methods. This review will present recent data from clinical and animal studies showing how altered TJ protein expression is a feature of certain CRCs. The up-regulation of claudin-1 in many CRCs is especially noteworthy. The focus of this article is simply on the association – however imperfect – between CRC and the major TJ transmembrane barrier proteins, namely claudins and occludin. Any causal relationship between TJ protein change and neoplasia remains conclusively unproven at present.